Internal user perception of service quality in a public institution - Sarmiento Prieto, Suseyla Roxana (2019)
This is a quantitative, descriptive and comparative study conducted on a sample of 310 public servants that attempts to describe the perception of service quality of the internal user via the following factors: cooperation between internal users, leadership of management, corporate social responsibility and performance self-appraisal. This study defines the internal user as any collaborator holding a position in the organizational structure. The valid and reliable five-degree EPCSU-IP ordinal scale was used for this research. The total perception is at a neutral level (3.54) with a tendency to higher degrees; it tends to be favorable in the dimensions of cooperation between internal users (3.67) and performance self-appraisal (3.73), and unfavorable regarding the factors leadership of management (3.45) and corporate social responsibility (3.27). The variable is studied as an indicator of the organizational climate in relation to the management of production processes of goods and services.